Unveiling the Impact of Morphine on Tamoxifen Metabolism in Mice in vivo - Gabel, Florian; Aubry, Anne-Sophie; Hovhannisyan, Volodya; Chavant, Virginie; Weinsanto, Ivan; Maduna, Tando; Darbon, Pascal; Goumon, Yannick (Frontiers in Oncology, 2020)
Background- Tamoxifen is used to treat breast cancer and cancer recurrences. After administration, tamoxifen is converted into two more potent antitumor compounds, 4OH-tamoxifen and endoxifen by the CYP3A4/5 and 2D6 enzymes in human. These active compounds are inactivated by the same UDP-glucuronosyltransferases isoforms as those involved in the metabolism of morphine. Importantly, cancer-associated pain can be treated with morphine, and the common metabolic pathway of morphine and tamoxifen suggests potential clinically relevant interactions. Methods- Mouse liver microsomes were used to determine the impact of morphine on 4OH-tamoxifen metabolism in vitro. For in vivo experiments, female mice were first injected with tamoxifen alone and then with tamoxifen and morphine. Blood was collected, and LC-MS/MS was used to quantify tamoxifen, 4OH-tamoxifen, N-desmethyltamoxifen, endoxifen, 4OH-tamoxifen-glucuronide and endoxifen-glucuronide. Results- In vitro, we found increased Km values for the production of 4OH-tamoxifen-glucuronide in the presence of morphine, suggesting an inhibitory effect on 4OH-tamoxifen glucuronidation. Conversely, in vivo morphine treatment decreased 4OH-tamoxifen levels in the blood while dramatically increasing the formation of inactive metabolites 4OH-tamoxifen-glucuronide and endoxifen-glucuronide. Conclusions- Our findings emphasize the need for caution when extrapolating results from in vitro metabolic assays to in vivo drug metabolism interactions. Importantly, morphine strongly impacts tamoxifen metabolism in mice. It suggests that tamoxifen efficiency could be reduced when both drugs are co-administered in a clinical setting, e.g. to relieve pain in breast cancer patients. Further studies are needed to assess the potential for tamoxifen-morphine metabolic interactions in humans.